2017
DOI: 10.29312/remexca.v6i7.553
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de 35 cultivares de haba por su producción de vaina verde y otros componentes del rendimiento

Abstract: El cultivo de haba en los Valles Altos del Centro de México, para la producción en vaina verde o para seco, es importante para los habitantes de escasos recursos. Este estudio se hizo en otoño -invierno de 2011 en San Francisco Oxtotilpan y en primavera- verano de 2012 en San Nicolás Guadalupe y en San Diego, México, para evaluar 35 cultivares de haba en un diseño experimental de bloques completos al azar con tres repeticiones por localidad. En las 12 variables evaluadas se detectaro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…This study found out that 93% of the farmers believe that seed health is the main criterion for the selection of the biological material that will be used in the next production cycle, while 55% consider that both the health and the size of the seeds are important. Additionally, Pérez-López et al (2015) suggest that the selection process should take into consideration the phenotypical expression (stem length, branches per plant, pods per plant, seeds per pod, and weight of 100 seeds).…”
Section: Resultsmentioning
confidence: 99%
“…This study found out that 93% of the farmers believe that seed health is the main criterion for the selection of the biological material that will be used in the next production cycle, while 55% consider that both the health and the size of the seeds are important. Additionally, Pérez-López et al (2015) suggest that the selection process should take into consideration the phenotypical expression (stem length, branches per plant, pods per plant, seeds per pod, and weight of 100 seeds).…”
Section: Resultsmentioning
confidence: 99%